Leptogium denticulatum (Collemataceae, lichenized Ascomycota) and some morphologically related species - Kitaura, Marcos Junji; Marcelli, Marcelo Pinto; Hora, Bianca Regina da [UNESP]; Jungbluth, Patricia (Amer Bryological Lichenological Soc Inc, 2015)
Leptogium specimens from all over the world with smooth to rugulose upper surface and flat, rotund and elongated lobules or denticules on the thallus or apothecia have been commonly identified as Leptogium denticulatum. However, Leptogium denticulatum has denticules only on the margin of the apothecia and is not a pantropical species. Leptogium brasiliense is considered a synonym of L. denticulatum. Leptogium mastocheilum, until now considered a variety of L. moluccanum, is recognized as a separate species. Specimens identified as L. denticulatum from Brazil, New Zealand and the U.S.A. are herein described as the new species L. atlanticum, L. oceanianum and L. joergensenii.
Keywords: Denticules; Lichen taxonomy; Lobules; Plectenchymatous tissue